Influences of temperature and humidity on cardiovascular disease among adults 65 years and older in China - Chen, Huashuai; Zhang, Xuebin (Frontiers in Public Health, 2023)
Background: The burden of cardiovascular disease (CVD) on the current aging society in China is substantial. Climate change, including extreme temperatures and humidity, has a detrimental influence on health. However, epidemiological studies have been unable to fully identify the association between climate change and CVD among older adults. Therefore, we investigated the associations between temperature and relative humidity and CVD among older adults in China. Methods: We used cohort data from the China Longitudinal Health and Longevity Survey (CLHLS) conducted in 2002, 2005, 2008, 2011, 2014, and 2018. A total of 39,278 Chinese adults 65 years and older participated in the analyses. The average annual temperatures and relative humidity during 2001 and 2017 (before the survey year) at the city level in China were used as the exposure measures. We selected patients with hypertension, heart disease, and stroke to create a sample of CVD patients. The associations between temperature and relative humidity and CVD were analyzed using the generalized estimation equation (GEE) model. Covariates included sociodemographic factors, health status, lifestyle, and cognitive function. Results: The average annual temperature was negatively correlated with the prevalence of CVD. Every 1℃ increase in the average annual temperature reduced the rates of hypertension by 3% (odds ratio [OR]: 0.97; 95% confidence interval [CI]: 0.96–0.97), heart disease by 6% (OR: 0.94; 95% CI: 0.92–0.95), and stroke by 5% (OR: 0.95; 95% CI: 0.94–0.97). The results of the analyses stratified by sex, urban/rural residence, and educational level were robust. The average annual relative humidity was inversely associated with the likelihood of CVD among older adults. Every 1% increase in the average annual relative humidity reduced the rates of hypertension by 0.4% (OR: 0.996; 95% CI: 0.99–1.00), heart disease by 0.6% (OR: 0.994; 95% CI: 0.99–1.00), and stroke by 0.08% (OR: 0.992; 95% CI: 0.98–1.00). However, the effects were more obvious with higher humidity levels (>70). Conclusion: Our findings suggest that higher temperatures and relative humidity may reduce the risk of CVD among older adults.